Tools for Development : Public Sector Governance Reform - Wilhelm, Vera A.; Kushnarova, Inna (World Bank, Washington, DC, 2012)
This CE Brief proposes the Public Sector Governance Reform Cycle framework to help Bank staff and clients identify tools and techniques to assess and strengthen capacity in the public sector. A number of lessons and challenges have emerged: Tools relying on large sets of microdata benefit from both quantitative and qualitative data. Highly aggregated data are useful for cross-country comparisons and awareness raising, while design of sector-specific reform programs requires specific and disaggregated data. Employing a wide range of data sources and tools and triangulating results can greatly enhance reform programs, whereas quality control will enhance credibility of results. The degree of impact on policy debate and capacity building depends on client demand, openness, participation, and transparency. It is important to move beyond governance diagnostics to implement reforms and measure progress against poverty reduction targets.